Translational research on advanced therapies - Filippo Belardelli; Paola Rizza; Franca Moretti; Cintia Carella; Maria Cristina Galli; Giovanni Migliaccio (Istituto Superiore di Sanità, 2011)
Fostering translational research of advanced therapies has become a major priority of both scientific community and national governments. Advanced therapy medicinal products (ATMP) are a new medicinal product category comprising gene therapy and cell-based medicinal products as well as tissue engineered medicinal products. ATMP development opens novel avenues for therapeutic approaches in numerous diseases, including cancer and neurodegenerative and cardiovascular diseases. However, there are important bottlenecks for their development due to the complexity of the regulatory framework, the high costs and the needs for good manufacturing practice (GMP) facilities and new end-points for clinical experimentation. Thus, a strategic cooperation between different stakeholders (academia, industry and experts in regulatory issues) is strongly needed. Recently, a great importance has been given to research infrastructures dedicated to foster translational medicine of advanced therapies. Some ongoing European initiatives in this field are presented and their potential impact is discussed.